1998
DOI: 10.1111/j.1528-1157.1998.tb01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Verbal Memory Loss in Individuals After Anterior Temporal Lobectomy

Abstract: Summary:Purpose: Decreased memory function represents the area of greatest neuropsychological morbidity after anterior temporal lobectomy (ATL), particularly for left ATL candidates. We wished to identify easily derived demographic and neuropsychological predictors of risk of pre-to postoperative memory decline using only information available preoperatively.Methods: We assessed decline in memory as measured by the California Verbal Learning Test (CVLT) by deriving multiple regression equations using the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 48 publications
8
51
0
2
Order By: Relevance
“…According to this approach, the central nervous system is considered as an integrated, wide, plastic network made up of cortical functional epicenters (i.e., 'topic organization') connected by both local and much longer white matter fibers (i.e., 'hodological organization'; De Benedictis and . According to this view of brain organization, cognitive functioning reflects the processing of parallel streams of information, which are dynamically modulated across interactive, multimodal, widely distributed circuits (including cortico-cortical and cortico-subcortical circuits; Davies et al, 1998). This new approach is supported by recent clinical observations demonstrating that it is possible to safely remove regions traditionally considered inoperable without inducing permanent deficits (Duffau, 2010).…”
Section: General Considerationsmentioning
confidence: 64%
See 1 more Smart Citation
“…According to this approach, the central nervous system is considered as an integrated, wide, plastic network made up of cortical functional epicenters (i.e., 'topic organization') connected by both local and much longer white matter fibers (i.e., 'hodological organization'; De Benedictis and . According to this view of brain organization, cognitive functioning reflects the processing of parallel streams of information, which are dynamically modulated across interactive, multimodal, widely distributed circuits (including cortico-cortical and cortico-subcortical circuits; Davies et al, 1998). This new approach is supported by recent clinical observations demonstrating that it is possible to safely remove regions traditionally considered inoperable without inducing permanent deficits (Duffau, 2010).…”
Section: General Considerationsmentioning
confidence: 64%
“…There is also evidence that an EZ in or near the hippocampal region but distant from temporal language regions may modulate the lateralization of language representation Hamberger et al, 2007). Compared with patients without HS, patients with HS are more likely to show atypical hemispheric lateralization of language (Pataraia et al, 2004;Powell et al, 2008;Labudda et al, 2010;Richardson, 2010) and have better language functioning (Chelune et al, 1991;Hermann et al, 1995;Davies et al, 1998;Stroup et al, 2003;Gleissner et al, 2004;Baxendale et al, 2006;Lineweaver et al, 2006). As suggested by Knecht (2004), the hippocampus may be crucial to the implementation of hemispheric lateralization for language, and frontotemporal language network functioning may be altered if the hippocampus is injured.…”
Section: Interindividual Factorsmentioning
confidence: 97%
“…Whereas older patients who undergo SAH will not lose much more than younger patients, older ATL patients experience significantly greater losses than patients who underwent surgery at younger age. 5 This is graphically demonstrated by the fact that, according to the regression lines, after left ATL a 20-year-old patient showed the memory performance of a 40-year-old patient treated with medical means alone (loss of 20 years). The equivalent loss in a 30-year-old patient was over 40 years (see the left scatter plot for ATL in Fig 2).…”
Section: Fig 1 Preoperative and Postoperative Performance In Verbal mentioning
confidence: 98%
“…[3][4][5] It is also well recognized that memory, in particular those aspects which require flexibility and speed, decline with advancing age. 6 We recently showed that in patients with mesial left hemisphere TLE, this lifetime memory decline is parallel to that observed in the general population, suggesting that the course of memory in pharmacologically treated TLE is better explained by the combined effects of underlying brain lesion and "normal" aging than by progressive brain damage due to chronic epilepsy.…”
Section: Ann Neurol 2002;52:89 -94mentioning
confidence: 98%
“…Despite these limitations, presurgical neuropsychological data remain valuable in the prediction of postsurgical functioning, 31 and neuropsychological tasks are a critical component of the intracarotid amobarbitol procedure.…”
Section: Commentmentioning
confidence: 99%